Pengaruh Pengalaman Kerja, Akuntabilitas dan Tekanan Waktu terhadap Kualitas Audit Internal: Studi Empiris pada Perusahaan BUMN dan BUMS di Kota Padang - Patricia Monita Malau; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to determine the effect of work experience, accountability and time pressure on the quality of internal audits in BUMN and BUMS companies in Padang City. The sampling technique in this study used purposive sampling method. Based on certain criteria. Obtained a sample of 45 respondents. The statistical method used is multiple linear regression. The results showed that the contribution of the independent variable was only 10.3% of the dependent variable. The result of hypothesis testing is that t is small from t table so that work experience, accountability and time pressure have no significant effect on the quality of internal audits in BUMN and BUMS companies in Padang City. For further researchers, it is recommended to use different variables and expand the research sample.